Fast‐tracking the evaluation of novel female candidate lines in CMS‐based hybrid breeding. (3rd May 2021) - Trini, Johannes; Maurer, Hans Peter; Weissmann, Elmar A.; Würschum, Tobias
Abstract: Time‐ and resource‐efficient identification of promising lines is of utmost importance in hybrid breeding. Here, we present a novel approach to evaluate female candidate lines for single‐cross hybrids, which saves four to five generations by obtaining general (GCA) and specific combining ability (SCA) effect estimates prior to the introgression of the female lines into a male sterility‐inducing cytoplasm. The approach is based on three‐way crosses and we exemplarily demonstrate its power by predicting 57 single‐cross hybrids of triticale. Prediction accuracies based on GCA or GCA and SCA effects estimated in three‐way hybrids were generally superior to those based on mid‐parent values. Notably, a high proportion of SCA variance had only little influence on the prediction accuracies based on three‐way hybrids. Simulation studies support the empirical findings and illustrate approaches for further optimization. Thus, the presented approach appears highly valuable and has the potential to increase selection gain in hybrid breeding.